Investigating Performance Zero-Forcing of Source Weighting Matrix in MIMO Relay Communication - Apriana Toding; Rismawaty Arungla'bi (Prosiding International conference on Information Technology and Business (ICITB), 2015)
In this paper, we study the zero forcing (ZF) algorithm fora two hop multiple-input multiple-output (MIMO) relaycommunication system consisting of one source node, onerelay node, and one destination node. We consideramplify-and-forward (AF) strategy at relay node anddestination node, respectively. We propose Pre-ZFequalization on the transmitter side. We have evaluatedthe proposed system by comparing with existingalgorithms. The proposed Pre-ZF equalization algorithmhas a significant improvement in the system bit-error-rate(BER) performance.Key words: multiple-input multiple-output (MIMO),MIMO relay networks, relay system, beamforming, zeroforcing.